Organizational Culture and Emotional Intelligence on Employee Creativity - Sumiyati, Sumiyati; Slamet Riyanto, Agus; Zaharuddin, Zaharuddin; Supriyadi, Supriyadi (International Journal of Business, Law, and Education, 2025)
Development and change in an organization as long as the organization exists is an inevitability that cannot be avoided. This research aims to reveal the influence of organizational culture and emotional intelligence on employee creativity. This research is quantitative research with a survey approach. The population in this study were all lecturers and educational staff at Panca Sakti University, Bekasi. The sampling technique used in this research was random sampling. Research data was obtained through organizational culture instruments, emotional intelligence instruments and employee creativity instruments. Before the instruments were used, validity and reliability tests were carried out. The results of instrument testing obtained a valid and reliable instrument. The research results can be concluded 1). Organizational culture has a positive effect on employee creativity; 2). Emotional intelligence has a positive effect on employee creativity; 3). Organizational culture and emotional intelligence stimulantly have a positive influence on employee creativity; The influence of organizational culture and emotional intelligence variables on employee creativity is 83.2%.